Affirmative Intervention to Reduce Stereotype Threat Bias: Experimental Evidence from a Community College. (28th July 2020) - Baker, Dominique J.; Skinner, Benjamin T.; Redding, Christopher H.
ABSTRACT: At all levels of education, the racial achievement gap in performance between Black and Latino students and their White peers stubbornly persists. While the causes of this gap are numerous and interrelated, one theory posits that students from underrepresented racial groups may face stereotype threat, meaning that fear of failing and thereby fulfilling negative group stereotypes leads to anxiety and suboptimal cognitive performance. Though low-cost value affirmation interventions have been shown to reduce achievement gaps in some classroom settings, these findings have not been consistently replicated. In this study, we test the efficacy of this intervention among a new sample of students enrolled in a community college in the Midwest. At the beginning of the fall 2016 semester, students in English courses (N = 1, 115 in 59 course sections) were randomly assigned to short writing exercises that were either self-affirming or neutral. Using administrative data collected at the end of the term, we compared treatment and control students on a range of outcomes that included course grade, overall GPA, and course persistence. Overall, we find little evidence of a positive effect of this one-time affirmation of social identity. Moderation analyses, however, show heterogeneous effects across course sections, suggesting that the classroom setting may play a role in the interaction between social identity and student outcomes.